Memory, Poetry and Subjetivity in Alicia Genovese’s Writing (Letras, 2019)
This work aims to propose a reflection on the relationship among memory, poetry, and subjectivity in the poetry and essays by Argentine poet Alicia Genovese (Lomas de Zamora, Province of Buenos Aires, Argentina, 1953), focusing on the intertextual dialogues established between both textualities. In order to expose this argument, I shall study both the essays as well as the poetry that Genovese has developed since the late 1990s to the present, which is marked by memory as one of its main topics. This is a characteristic, however, that not only responds to the personal options of the poet, but that has to be referred to the context of writing, which is defined, on the one hand, by the deep socio-political crisis of 2001, and, on the other hand, by the development of intense social debates about the memories of Argentine recent past.
Keywords: Argentine Poetry; Alicia Genovese; Memory; Subjectivity